Development and validation of a nomogram to predict liver metastasis for pancreatic ductal adenocarcinoma after radical resection - Tong, Jingshu; Jiang, Wei; Mao, Shuqi; Wu, Shengdong; Lu, Caide (Frontiers in Oncology, 2022)
Objectives: This study aimed to develop and externally validate a nomogram for predicting liver metastasis after radical resection in patients with pancreatic ductal adenocarcinoma (PDAC). Methods: A total of 247 PDAC patients who underwent radical resection were retrospectively reviewed from January 2015 to March 2022 at Ningbo Medical Centre Lihuili Hospital Eastern Section, and used as a training cohort to develop the nomogram. 83 PDAC patients from the Lihuili Hospital Xingning Section were enrolled as the validation cohort. The postoperative liver metastasis was recorded during the follow-up, and the liver metastasis-free survival was defined as the time from operation to the date of liver metastasis diagnosis or death. The nomogram was established based on independent prognostic factors selected by LASSO and Cox model. The performance was assessed using the concordance index (C-index) and calibration curves. The area under receiver operating characteristic (AUC) curve and decision curve analysis (DCA) were used to determine the clinical utility of the nomogram model.. Results: From the training cohort of 247 patients, the 1- , 2- and 3- year liver metastasis-free survival were 52.4%, 43.5% and 40% respectively. The LASSO and multivariate Cox regression analysis indicated that postoperative CA125 (hazard ratio [HR] = 1.007, p <0.001), tumor differentiation (HR=1.640, p=0.010), tumor size (HR=1.520, p=0.029), lymph node ratio (HR=1.897, p=0.002) and portal/ superior mesenteric/ splenic vein invasion degree (PV/SMV/SV) (HR=2.829, p<0.001) were the independent factors of liver metastasis. A nomogram with independent factors was developed and the C-index was 0.760(95%CI, 0.720-0.799) and 0.739(95%CI, 0.669-0.810) in the training and validation cohorts, respectively. AUC of the nomogram at 1-,2-and 3-year were 0.815, 0.803 and 0.773 in the training cohort, and 0.765, 0.879 and 0.908 in the validation cohort, respectively, higher than those in TNM stage. DCA analysis revealed that the nomogram model provided superior net benefit in clinical utility. Liver metastasis-free survival curves showed a significant discriminatory ability for liver metastasis risk based on the nomogram (p<0.001). Conclusions: The nomogram showed high accuracy in predicting liver metastasis for PDAC after radical resection, and may serve as a clinical support tool to guide personalized and prescient intervention.